Answer: 4x² + 4x - 2 - ![\frac{3}{2x+3}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B2x%2B3%7D)
<u>Step-by-step explanation:</u>
You can use either synthetic or long division. I am using synthetic division:
2x + 3 = 0 ⇒ x = ![-\frac{3}{2}](https://tex.z-dn.net/?f=-%5Cfrac%7B3%7D%7B2%7D)
| 4 10 4 -6
<u>| ↓ -6 -6 3 </u>
4 4 -2 -3 ← <em>-3 is the remainder</em>
↓ ↓ ↓
4x² +4x -2 ← <em>factored polynomial</em>
Answer:
13
Step-by-step explanation:
- f(x) = (x-13)(x+6)
- x^2 - 7x - 78
- x = 13, -6
In step 1, the commutative property of addition is used since x + 5 is just equal to 5 + x
In step 2, the associative property of addition is used since x is grouped to the last term.
In step 3, the distributive property of multiplication is used since 3 is multiplied to the terms inside the parenthesis.
In step 4, multiplication is done.
The answer probably would be this 5ab-5ac=d